Myocarditis with neurological and dermatological involvement in idiopathic Hypereosinophilic syndrome: Case report - Merimi Ihssane; Mrabet Asmae; Abarkane Nisrine; Bennesser Alaoui Habiba; Noha Elouafi; Nabila Ismaili (Radiology Case Reports)
Eosinophilic myocarditis (EM), irrespective of its unique etiology, is marked by varying extents of eosinophil infiltration, frequently accompanied by peripheral eosinophilia.In some instances, the etiology remains undetermined, thus classified as idiopathic hypereosinophilic syndrome. The clinical manifestations are highly variable, ranging from mild or asymptomatic presentations to acute fulminant myocarditis or chronic restrictive cardiomyopathy.We report a case of idiopathic hypereosinophilic syndrome, characterized by eosinophilic myocarditis, alongside axonal and dermatological involvement. During the follow-up period, the patient demonstrated significant clinical and echocardiographic improvement under corticotherapy and heart failure management, including normalization of eosinophil counts.